Comparison the Effect of Rosella Flower Extract Mouthwash (Hibiscus Sabdariffa L.) and Chlorhexidine on Saliva Ph of Students Department of Dental Health, Poltekkes Palembang - Ismalayani; Sri Wahyuni (East Asian Journal of Multidisciplinary Research, 2023)
Dental and oral health problems based on The Global Burden Disease in 2016 stated that dental caries is still experienced by almost half of the world's population. One of the factors causing caries is salivary pH. This research is an experimental research with pre and post test designs. The research sample of students from the Department of Dental Health is 100 samples taken by simple random sampling. Data were analyzed using univariate test and multivariate test using One Way Anova Test followed by Post Hoc Test. Based on the results of the study, it was found that in the One way Anova test there was a significant difference in the average of gargling with rosella flower extract mouthwash 20%, 40%, 60%, and chlorhexidine on salivary pH, but based on the Post Hoc test, rosella flower extract mouthwash 20 % as effective as 40% rosella flower extract mouthwash, but different from 60% rosella flower extract mouthwash. Thus, it was concluded that the effectiveness of 60% rosella flower extract mouthwash was significantly stronger in increasing salivary pH than Chlorhexidine mouthwash, this was shown in statistical test.